P126 Distanced-learning basic skills in ERCP course: trainee feedback and effectiveness at delivering the JAG curriculum. (19th June 2022) - Phillpotts, Simon; Menabawey, Tareq El; Martin, Harry; Webster, George; Johnson, Gavin
Abstract : Introduction: Distanced learning has become common place in recent years. This online basic skills in ERCP course was developed in line with the JAG training pathway and certification standards. Considering previous JAG approved courses have been hands-on, we assessed whether a distanced learning format is effective at meeting trainee expectations and curriculum learning outcomes. Methods: The course was delivered to 8 delegates through an online platform. Four half-day sessions introduced the theory and practical aspects of ERCP training, covering: pre-procedure, intra-procedure and post-procedure topics. Although not a hands-on course, the format was based on recorded cases to highlight the different learning points. Feedback, in the form of Likert scales (strongly disagree (1), disagree (2), neutral (3), agree (4), strongly agree (5)) assessed the effectiveness of the course at delivering learning outcomes drawn from the JAG curriculum, and whether it was suited to a distanced learning format. Pre and post course questionnaires asked delegates their confidence in managing the different learning outcomes. Results: Feedback for the course format was positive, with agreement that it was suitable for theory-based learning (median response 4.0). There were mixed views regarding the separation of theory and practical content, and whether this was detrimental to learning (3.0). Overall, there was agreement that this course is useful for training (5.0) and would be recommended to a colleague (5.0). Post-course responses were more positive than those pre-course for all learning outcomes. Particularly notable was the shift from disagreeing (pre-course) to agreeing (post-course) about confidence in biliary cannulation techniques (2.0 to 4.0), methods for cannulation when selective cannulation fails (2.0-4.0), biliary stent choices (2.0-4.5), and on the spot decisions about managing jaundiced patients (2.5-4.0). Conclusion: JAG certification in ERCP will soon require attendance on basic skills courses and e-learning has been proposed as a novel way to deliver such courses in the recovery of endoscopy training following Covid-19. Feedback for this distanced learning course suggests this format is suitable for the theory-based learning, improving participants confidence in managing specific aspects of ERCP theory and knowledge. Further courses are needed to assess the impact on a wider audience, and a longer follow would allow evaluation of the impact on the ERCP learning curve.